Sinais de dotação em estudantes medalhistas da Obmep: um estudo de caso - Oliveira, Lais Paloma de (2020)
Brazil has a low number of enrollments of students with Giftedness and Talent in basic education, in view of the numbers suggested in the literature of the area on the incidence of the phenomenon. The Brazilian Mathematics Olympiad of Public Schools (OBMEP) is a competition that reaches an expressive number of students in the country, rewarding those who obtain better performances in their tests. The general objective of this research was to investigate and analyze the existence of giftedness signs in students who have participated and won medals in one of the editions of OBMEP in two cities in the inland of the state of São Paulo. The specific objective was to compare characteristics proposed in the literature on Giftedness and Talent in mathematics and the signs of Giftedness observed in medalists. The study was characterized as qualitative, being a multiple case study. Two OBMEP medalist students and four teachers participated in the research. The data were collected by the teachers' responses to the Direct Observation Guide in the Classroom, considering classes with OBMEP medalist students for whom they taught. The academic results of the medalist students were also used and in one of the case studies there was an interview. The results suggest the existence of Giftedness signs in both medalists in the intellectual domain and the students' academic evaluations expressed above average. The two students investigated were indicated in the same ten (10) items, in the Observation Guide of a total of 31, and, all of these characteristics are similar to the literature descriptions about students with Giftedness, especially in the mathematical area. The interview applied to one of the medalist students also met the indications of the specialized literature in the area of Giftedness, as it was possible to find important similarities between characteristics of Intellectual Giftedness and the signs observed and indicated by the teachers of the medalist students. In the interview, it became clear the need to consider the student's interest in the topic when promoting the development of skills. Despite the limitations regarding the instruments used and the time to carry out the study, it was found that they are potential to advance in the identification of students with Intellectual Giftedness if the excellent performance of some students at OBMEP is considered.